Pemberdayaan PKK Desa Selok Anyar Melalui Pemanfaatan Platform Digital Berbasis Bahasa Inggris untuk Mendukung Program Desa Digital - Kurnia, Lely Indah; Rozaq, Mutrofin; Setyawan, Bimo; Mustofa, Ahmad; Khoirunisa, Rizqi; Purnomo, Subekhi Hadi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
The rapid development of digital technology has created new opportunities and challenges for rural communities, particularly in improving digital literacy and communication skills. In Desa Selok Anyar, members of the Family Welfare Empowerment (PKK) group still face limited understanding of English-based digital platforms, which hinders their participation in the village digitalization program. This community service activity aimed to empower PKK members through training on the use of English-based digital platforms to support the realization of a digital village. The methods applied included socialization, workshops, mentoring, and evaluation. The results showed a significant improvement in participants’ ability to operate digital applications, understand English terms commonly used in online platforms, and promote local products more effectively. In addition, the participants demonstrated increased confidence in utilizing technology to support economic and tourism activities in the village. This program successfully enhanced digital literacy and English competence among PKK members, contributing to sustainable community empowerment and the development of a digital-based village.